Análise da formação de Complexos Regionais de Segurança (CRS): um estudo comparativo entre a América do Sul e o leste asiático - Shin, Myung Joo [UNESP] (2015)
Regionalism became a new trend in the international politics in the 21th century, and it was predominated in the area of security and defense as well. In East Asia, perceptions of security are still more linked to those traditional issues, such as the expansion and the acquisition of arms, the nuclear issue of North Korea and territorial conflicts. On the other hand, in the case of South America, countries pay more attention to issues relating to the non-military sector such as drug trafficking, the environment and human rights. In this paper, we check the caracteristics and differences between East Asia and South America through the concept of Regional Security Complex (RSC) for the views through history, theories and institutions. It is proposed to analyze these differences in terms of the intensity of threats, from four types of elements: specificity of the threat, probability of realization, existence of historical experience and cordial relationship between the countries of two regions. The aim of this study is to analyze and evaluate the formation of both CRS of South America and East Asia and understand how each region understand the security problems.